Promoting Semanggi Surabaya as an Icon and Tourist Attraction of Surabaya City - Bawa Mulyono Hadi (Dinasti International Journal of Education Management And Social Science, 2024)
The purpose of this research is to promoting Semanggi Surabaya as an icon and tourist attraction in the city of Surabaya. The research design is a case study. Data collection techniques include observation, interviews, and documentation. Data analysis is conducted using the Miles Huberman method. Promoting Semanggi Surabaya as an icon and tourist attraction in the city of Surabaya signifies an effort to enrich its cultural identity. By highlighting the beauty and uniqueness of clover as a symbol representing fertility, peace, and luck, Surabaya expands the awareness of tourists regarding its hidden natural tourism potential. This initiative not only promotes the beauty of the local nature but also strengthens the local community's pride in their cultural heritage. The conclusion emphasizes the importance of preserving and promoting local cultural elements as a strategy to enhance the tourism industry of a city while fostering awareness of the significance of environmental preservation and cultural identity in the rapidly advancing context of globalization.